PERANCANGAN SIS+ MENGGUNAKAN METODE YII FRAMEWORK PADA PERGURUAN TINGGI RAHARJA - Ary Budi Warsito; Muhamad Yusup; Moh. Iqbal Awi Makaram (Universitas Raharja, 2015)
The development of information technology is increasingly rapidly and constantly changing year after year requires us to constantly innovate and make a creative work, as well as Higher Education Prog desperately need information systems that are relevant, accurate, fast, and efficient to support the sustainability of academic activity future. The author conducted research on SIS Information Systems in college Prog. The research method used was observation, library research and documentation. Development method used is the waterfall method. Based on the analysis conducted by the author and the problems encountered in the use of the SIS is still menggukan sweep sweep card card if the card is damaged / lost then the student can not use the SIS, the SIS is still accessing performed locally where the student must come in person to the SIS Box to take care of matters related to the students academic activity and as one of the alternative solutions, then be made to the proposed development of the SIS system itself. SIS+ software is a web-based information systems and made by Yii Framework using the PHP programming language. Database management system (DBMS) used in this software is MySQL. This information system will display the data that include academic values list data, student biographical data form and the form needed by the students, in addition, an information system is also expected to boost the quality and service to students.